2003
DOI: 10.1097/00024720-200302000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Sacroiliac Joint: A Potential Cause of Pain After Lumbar Fusion to the Sacrum

Abstract: The sacroiliac joint (SIJ) can cause pain after lumbosacral fusion. Diagnosis requires >75% relief after local anesthetic SIJ injection. This study is a retrospective review of patients with low back pain after lumbosacral fusion who had SIJ injections. Percentage and duration of pain relief were noted. Results are as follows: there were 34 patients; 8 fused at L5-S1, 14 fused at L4-S1, and 12 had multilevel fusions. Twenty had >75% relief within 45 minutes, and 11 had prolonged relief. Six had relief >20% but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 19 publications
3
122
1
6
Order By: Relevance
“…In comparison to open sacroiliac joint fusion, the complication profile is acceptable [20]. The prevalence of sacroiliac joint involvement in post fusion low back pain ranges from 29 to 40 % [21,22]. This is likely to be due to transfer of motion from the fused segment to the next mobile intact segment, which in the case of lumbar-sacral fusion would be the sacroiliac joint.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to open sacroiliac joint fusion, the complication profile is acceptable [20]. The prevalence of sacroiliac joint involvement in post fusion low back pain ranges from 29 to 40 % [21,22]. This is likely to be due to transfer of motion from the fused segment to the next mobile intact segment, which in the case of lumbar-sacral fusion would be the sacroiliac joint.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the facet and iliosacral joints to be a source of post-operative pain in a considerable number of patients [29,42,43]. Alterations of the segmental, sagittal and spinopelvic alignment as well as increased motion and stress adjacent to fused levels have been held responsible for post-fusion pain patterns [1,21,29,32,42,43,63].…”
Section: Discussionmentioning
confidence: 99%
“…1-1.5 ml for a facet joint infiltration and 2-3 ml for an infiltration of the iliosacral joint. All infiltrations were performed as direct joint infiltrations as described previously [18,19,29,31,42,43].…”
Section: Injection Techniquementioning
confidence: 99%
See 2 more Smart Citations